Famine and disease in Ireland
1 online resource (5 volumes)
Keywords: This collection contains Five volumes of reprints of contemporary works relating to the Great Famine, including writings on the medical conditions in Ireland at the time gathered from the "Dublin Journal of Medical Science" and similar publications.